A complexity reduced and reliable integrity protection for large relational data over clouds. (25th May 2021) - Haider, Waqas; Nisar, Muhammad Wasif; Saba, Tanzila; Sharif, Muhammad; Haider, Raja Umair; Bilal, Nadeem Muhammad; Khan, Muhammad Attique
At present, governments and private business operations are highly dependent on relational data applications such as bank accounts, citizen registration, etc. These relational data dependent operations require reliable integrity protection while utilising the cloud computing storage infrastructure. Identification and recovery of stolen bits are a major assistance to the reliable integrity protection services for the sensitive relational data applications. To deal with the problems of detecting and recovering tampering in large relational data at minimum computational complexity, in this paper, N8WA (briefed in Section 2.1) coding-based scheme is presented. Overall the scheme is comprised of two cross functional modules. The first module is labelled as compact code generation using N8WA coding and code registration at registration module (RM). In the second module which is called accurate locating/restoring tampering, utilising the mismatching of different compact codes based on N8WA from RM, the major/minor tampered data is accurately located and restored. Investigational outcome indicates that the scheme ensures the computational complexity of O ( n 2 ) while minimum to maximum alterations is accurately localised and restored successfully.